Optimization of THz diffractive optical elements thickness - Surma, Mateusz; Ducin, Izabela; Sypek, Maciej; Zagrajek, Przemyslaw; Siemion, Agnieszka (Photonics Letters of Poland, 2018)
Diffractive optical elements (DOEs) are strictly related to the design wavelength due to the fact that they must introduce particular phase delay of the wavefront propagating through the structure. Mostly the attenuation of the material is not taken into account. In this article we propose to optimize thickness of the DOE by reducing introduced phase retardation but also attenuation. The efficiency of DOEs is determined by the method of coding phase distribution and can be easily measured by using diffraction orders of corresponding diffraction grating. Here, we analyze binary phase diffraction gratings with assumed attenuation. Full Text: PDF References J.-L. Coutaz, Optoélectronique térahertz (Les Ulis CEDEX A, France, EDP Sciences 2012). DirectLink D. Headland, Y. Monnai, D. Abbott, C. Fumeaux,and W. Withayachumnankul, "Tutorial: Terahertz beamforming, from concepts to realizations", APL Photonics 3, 5 (2018). CrossRef S. F. Busch, M. Weidenbach, M. Frey, F. Schäfer, T. Probst, nd M. Koch, "A 3D-Printable Polymer-Metal Soft-Magnetic Functional Composite—Development and Characterization", Journal of Infrared, Millimeter, and Terahertz Waves 35, 12 (2014) CrossRef A. Siemion, P. Kostrowiecki-Lopata, A. Pindur, P. Zagrajek, M. Sypek, "Paper on Designing Costless THz Paper Optics", Advances in Materials Science and Engineering 2016, 9615698 (2016). CrossRef A. Siemion, A. Siemion, M. Makowski, J. Suszek, J. Bomba, A. Czerwinski, F. Garet, J.-L. Coutaz, and M. Sypek, "Diffractive paper lens for terahertz optics", Opt. Lett. 37, 4320–4322 (2012). CrossRef J.-L. Coutaz, F. Garet, E. Bonnet, A. V. Tishchenko, O. Parriaux, and M. Nazarov, "Grating Diffraction Effects in the THz Domain", Acta Phys. Pol. A 107, 26-37 (2005). CrossRef M. S. Heimbeck, P. J. Reardon, J. Callahan, and H. O. Everitt, "Transmissive quasi-optical Ronchi phase grating for terahertz frequencies", Opt. Lett. 35, 21 (2010). CrossRef D. Li, S. Shu, F. Li, G. Ma, Y. Dai, and H. Ma, "Anomalous transmission of terahertz wave through one-dimensional lamellar metallic grating", Opt. Commun. 284, 10-11 (2011). CrossRef X. Li, and S. F. Yu, "Diffraction Characteristics of Concentric Circular Metal Grating Operating at Terahertz Regime", IEEE Journal of Quantum Electronics 46, 6 (2010). CrossRef B. Nöhammer, C. David, J. Gobrecht, and H. P. Herzig, "Optimized staircase profiles for diffractive optical devices made from absorbing materials", Opt. Lett. 28(13), 1087-1089 (2003). CrossRef V. Deuter, M. Grochowicz, S. Brose, J. Biller, S. Danylyuk, T. Taubner, D. Grutzmacher, and L. Juschkin, "Holographic masks for computational proximity lithography with EUV radiation", International Conference on Extreme Ultraviolet Lithography 2018 10809, 108091A (2018). CrossRef J. W. Goodman, Introduction to Fourier optics (Greenwood Village, USA, Roberts & Company Publishers 2005). DirectLink W. B. Veldkamp, "Optimized staircase profiles for diffractive optical devices made from absorbing materials", Appl. Opt. 21(17), 3209-3212W (1982). CrossRef W. B. Veldkamp, and C. J. Kastner, "Beam profile shaping for laser radars that use detector arrays", Appl. Opt. 21(2), 345-356 (1982). CrossRef https://www.mcortechnologies.com/de/3d-drucker/mcor-iris/ DirectLink M. Sypek, M. Makowski, E. Hérault, A. Siemion, A. Siemion, J. Suszek, F. Garet, and J.-L. Coutaz, "Highly efficient broadband double-sided Fresnel lens for THz range", Opt. Lett. 37, 12 (2012). CrossRef